Teste tuberculínico em indivíduos com infecção pelo vírus da imunodeficiência humana: Relação com número de linfócitos T periféricos e atividade tuberculosa - De Souza, Lenice Do Rosário [UNESP] (2006)
Objective: To evaluate tuberculin test results and relate them to the presence or absence of active tuberculosis, as well as to CD4+ and CD8+ T-lymphocyte counts. Method: The charts of 802 patients with acquired immunodeficiency syndrome treated between August of 1985 and March of 2003 were reviewed. Of the 185 patients submitted to tuberculin tests (23.1%), 107 (57.8%) were male, and 78 (42.2%) were female. Patients were divided into two study groups: tuberculin test reactors (n = 28); and tuberculin test non-reactors (n = 157). Among the reactors, the mean age was 30.60 years, with a standard deviation of 6.62 years, compared with 34.45 years, with a standard deviation of 10.32 years, among the non-reactors. Results: Most of the individuals tested presented only a mild response to the tuberculin test. We found that, at the time of the test, the percentage of individuals with active tuberculosis was greater in the reactor group than in the non-reactor group. During the test period, 10 reactor group patients and 11 non-reactor group patients presented some clinical form of active tuberculosis. In addition, CD4+ T-lymphocyte counts were lower than 200 cells/mm3 in 6 reactor group patients and in 8 non-reactor group patients. Conclusion: Indurations greater than 5 mm were unrelated to higher absolute CD4+ T-cell counts.